2017
DOI: 10.1088/2040-8986/aa86d5
|View full text |Cite
|
Sign up to set email alerts
|

Design of mechanically robust metasurface lenses for RGB colors

Abstract: In recent years, dielectric rod based metasurface lenses have been particularly investigated for their potential applications in replacing the traditional bulky lens with high efficiency. However, the isolated granular structure may lead to robustness and chromatic aberration concerns. In this work, a low refractive-index embedding medium was applied to solve the structural stability problem that also enables the device to be transferable to desired position or surface. Based on this, a compound metasurface le… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Optical Mater. 2020, 8,1901523 www.advopticalmat.de the same setup (see Figure 4d,e). The reflected intensity image clearly manifests the outline of the letters.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Optical Mater. 2020, 8,1901523 www.advopticalmat.de the same setup (see Figure 4d,e). The reflected intensity image clearly manifests the outline of the letters.…”
Section: Resultsmentioning
confidence: 94%
“…Optical Mater. 2020, 8,1901523 www.advopticalmat.de the metasurface. The output field intensity patterns of the ideal device (the ideal transfer function H(θ) is given in Equation (2) with β = 42, the blue solid line) and the actual device (H(θ) is shown in Figure 1d, the blue dashed line) when the input field pattern at the metasurface interface is U 0 (x′) = exp[−(x′/w) 2 ] (w = 80λ) at θ 0 = 25.4° (black line) are given in Figure 2b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, Wen et al demonstrated a spherical-to-cylindrical variable lens or a lens-to-hologram variable device dependent on the helicity of the incident light. , In 2017, Mueller et al presented a method that can independently control the phase profile of orthogonal polarizations and experimentally demonstrated a circular polarization hologram and an elliptical polarization beam splitter in the visible . Microwave multifunctional metasurfaces with transmission and reflection EM response functions have been proposed by tailoring orthogonal polarizations. Besides this polarization multiplexing, the spatial multiplexing also enables versatile functionalities, such as controlling the dispersion properties of metasurfaces , and realizing a passive Janus metasurface that has two different functions for opposite incident directions . Furthermore, dynamical tuning, such as using microfluidic channels, , phase-change materials, elastic materials, , and electric resistor, has also been investigated to achieve multifunctional properties based on metasurfaces.…”
mentioning
confidence: 99%